Documents and domains: Aspects of Intercultural Education in English Language Teaching (ELT) in Portugal - Hurst, Nicolas; Franco, Carla (Linguarum Arena, 2021)
The early learning of English in the state school network in Portugal has been the subject of a wide debate, which has not been exhausted by the introduction of English teaching as a curricular subject in the 1st cycle, in 2015, and which has helped to develop the intercultural awareness of a greater number of children. The new programmes and guideline documents emanating from the Ministry of Education, where objectives and areas of learning have been redefined, have been discussed and changed since the supranational imposition of the Common European Framework of Reference in 2001, with increasing allusions to the intercultural domain in learning English. Likewise, all the academic literature, from authors such as Byram (2006; 2009) and Guilherme . (2006), points to the centrality of intercultural competence in the learning of citizenship and curriculum construction since the first years of schooling. This article seeks to analyze the extent to which these intentions and visions of the “Intercultural Domain” have been incorporated into the reference curriculum documents and, in turn, will be structuring the experience of learning the English language by Portuguese children.